The Effect of the Implementation of the 2013 Curriculum on Mathematics Learning Outcomes of N.1 High School Students Stu Jehe Pakpak Bharat Regency From 2015 - 2018 - Aritonang, Elsida (Sains Global Institut, 2019)
Based on the list of Mathematics grade X grade students from T.P 2015/2016 to T.P 2017/2018, there can be seen many significant and positive changes with an increase in students' mastery learning from 40.87% to 48.72% to 80.85%. In addition to increased learning completeness, the average student learning outcomes in mathematics also increased. There is a change in the involvement of students to discuss and cooperate with fellow friends in terms of solving problems given by the teacher. Changes in the activity of students to take part in learning mathematics. The seriousness of students in participating in learning has also increased. The activeness of students in answering oral questions has also increased. This is indicated by the increasing number of students who give correct answers. the activeness of students in completing homework is increasing. This is indicated by the increasing frequency of students completing homework on time. The activeness of students to appear in front of the class solving problems on the board also increased. Students begin to believe in themselves and have the ability to solve the problems given. Based on observation, the teacher has a problem where the students are very familiar with the conventional way, the teacher explains in front of the class while students listen, Building a conducive classroom atmosphere by involving students to be more active sometimes inviting a commotion in the classroom where students initially play more than learn. Building a sense of responsibility to students also becomes difficult because students' demands actually become reversed because the teacher explains a little subject matter and students are directed to further develop material insights through discussion activities and so on. The application of the 2013 curriculum also requires students to understand the implementation of the value of the knowledge acquired so that a variety of practical activities are needed as a tangible form of the implementation of students' mathematical knowledge